Primary Household Energy for Cooking and Heating in 52 Developing Economies - Kojima, Masami (World Bank, Washington, DC, 2021)
Recent household surveys from 52 developing economies that include questions about energy use show that the most commonly cited primary energy for cooking is wood, followed by gas, natural gas and, where natural gas is not available, liquefied petroleum gas (LPG), and then by electricity. Biogas use is rare, and the use of ethanol and solar cookers is essentially non-existent. Households in the economies with a very high share of the population relying on clean energy as the primary source for cooking overwhelmingly prefer gas over electricity. In two-thirds of the economies more than half of the rich cook with clean energy, again preferring gas over electricity. As income rises and natural gas infrastructure becomes better established, urban households shift from LPG to natural gas, leaving LPG primarily for rural households. By contrast, in low-income and some lower-middle-income economies even the rich cook primarily with charcoal or kerosene (usually preferring charcoal over kerosene), while LPG is used by some well-off urban households. In one out of every six economies less than one-tenth of the population in the top 20 percent cites clean energy as their primary energy source for cooking. The choice of gas is driven in many instances by historical fuel price subsidy policies, which in some cases have continued to this day. Where natural gas is not available and LPG has not been subsidized but electricity has historically been reliable and cheap, such as in Southern Africa, the rich cook with electricity. Aside from price and supply reliability, community-wide familiarity with a particular technology and fuel, and economies of scale arising from popular use, may be partially driving the pattern of each economy’s showing dominant preference for gas or electricity.